Air patrol - Teitelbaum, Michael (Pleasantville, N.Y. : Reader's Digest Children's Books, 2006)
It's helicopters to the rescue! Flying high in the sky, the Air Patrol copters are on the scene, whether it's a rescue on a snowy mountain or saving a ship full of stranded sailors. Take an exciting flight with the Tonka Air Patrol and discover the many exciting jobs helicopters do.
Board book.
OCLC
OCLC
Keywords: Helicopters -- Juvenile fiction; Helicopters; Fiction; Juvenile works